Correction: De Conti et al. Histological Lesions and Replication Sites of PCV3 in Naturally Infected Pigs. Animals 2021, 11, 1520 - Elisa Rigo De Conti; Talita Pilar Resende; Lacey Marshall-Lund; Albert Rovira; Fabio Augusto Vannucci (Animals, 2021)
The authors wish to make the following correction to this paper [...]